Analytical Hierarchy Process (AHP) Model Feedstock Selection on Producing the Sustainable Aviation Fuel - Prayitno, Prayitno; Novani, Santi; Fikri, Dimas R. A. (International Journal Labs, 2023)
Global energy business is shifting towards more sustainable alternatives fuels due to climate change issue. Countries, companies, and associations start to adopt energy sources with less emission and carbon footprints in their business portfolio, including the introduction of Sustainable Aviation Fuel (SAF) in the aviation industry. Indonesia had created regulation in SAF utilization as blend component in Jet Fuel by the Energy & Mineral Resources Ministry Regulation No.12/2015: 2% (2016), 3% (2020) and 5% (2025). Considering the projected domestic demand of Jet Fuel 6.730.000 KL in 2030, requirement of SAF in Indonesia will reach 337.000 KL. In the contrary, there is no current SAF production in Indonesia despite of its potential feedstock for SAF such as Crude Palm Oil (CPO) Refined Bleached Deodorized Palm Kernel Oil (RBDPKO), or Used Coking Oil (UCO). The research analyzed the business aspect of SAF product development, especially bio-feedstock selection. This paper selected the most optimum feedstock for SAF by Analytical Hierarchy Process (AHP) method with 5 selection criterias: feedstock availability, feedstock price, required capital expenditure (CAPEX), profitability and SAF marketability. A base scenario of “highly regulated and fastly adopted SAF” is selected as the reference of developing the strategy. This scenario is indicated by early warning signs such as establishment of GHG emission reduction framework, establishment of incentives framework and high SAF demand from airlines.